2021
DOI: 10.1007/s11695-021-05323-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Drawbacks of Single-Anastomosis Duodeno-Ileal Bypass After Sleeve Gastrectomy in a Tertiary Referral Bariatric Center

Abstract: Background The need for revisional procedures after sleeve gastrectomy (SG) for insufficient weight loss or weight regain, gastroesophageal reflux, or other complications is reported to be 18–36% in studies with 10-year follow-up. Single-anastomosis duodeno-ileal bypass (SADI) may be performed as a revisional procedure after SG. This study aims to evaluate the short- and mid-term outcomes of SADI after SG in a referral center for bariatric surgery. Materials and Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 49 publications
(65 reference statements)
2
23
0
1
Order By: Relevance
“…To our knowledge, this is the first metanalysis conducted to delineate the outcomes of single anastomosis duodeno-ileal bypass as a prospective alternative for weight reduction following SG [ 6 ]. One trend in bariatric surgery is to simplify procedures, leading to the creation of one-anastomosis surgery options such as one anastomosis gastric bypass (OAGB) as an alternative to Roux en Y gastric bypass (RYGB) and SADI as an alternative to DS [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, this is the first metanalysis conducted to delineate the outcomes of single anastomosis duodeno-ileal bypass as a prospective alternative for weight reduction following SG [ 6 ]. One trend in bariatric surgery is to simplify procedures, leading to the creation of one-anastomosis surgery options such as one anastomosis gastric bypass (OAGB) as an alternative to Roux en Y gastric bypass (RYGB) and SADI as an alternative to DS [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Newcastle-Ottawa Quality Assessment Scale ( Table 1 ) was used as an evaluation tool to assess non-randomized controlled trials (non-RCTs) [ 1 2 4 5 6 7 8 9 10 11 12 13 14 ]. The scale’s range varies from 0 to 9 stars.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that the increase of the biliary loop dangerously increases the risk of malnutrition by decreasing the total alimentary limb length (TALL) [3,4]. Our experience with 106 patients who underwent single anastomosis duodeno-ileal bypass (SADI) showed, on the one hand, the systematic manipulation of the whole intestine starting from the cecum can be responsible for iatrogenic perforation and, on the other hand, despite a short common intestinal loop, the results on weight loss can be disappointing [5]. A nonstandard OAGB with variable biliary limb length and/or an OAGB with a biliary limb > 200 cm does not facilitate re-operations for reflux resistant to medical treatment, nor does it facilitate re-operations for malnutrition or those in an emergency by a surgeon, sometimes from another center, who must adapt the intervention after a calculation of the biliary limb length with risk of injury to the gastro-jejunal anastomosis or to carry out a complex operation.…”
mentioning
confidence: 99%